Short Video Addiction and Life Satisfaction: Sequential Longitudinal Pathways via Loneliness and Anxiety - Turk Kurtca, Tugba; Dogru, Muhammet Can (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
The rapid growth of short video platforms (e.g., TikTok, Instagram Reels) has raised concerns about their potential impact on well-being. Despite their popularity, empirical research examining the long-term effects of short video addiction (SVA) on life satisfaction remains limited, and few studies have employed longitudinal designs to explore underlying longitudinal mechanisms. This study aimed to address these gaps by examining the sequential longitudinal pathways involving loneliness and anxiety between SVA and life satisfaction. A half-longitudinal design with two waves, spaced three months apart, was utilized. Data were collected from 234 participants (M-age = 22.02). A half-longitudinal cross-lagged panel model was employed to examine temporal and directional effects. Findings indicated that SVA predicted increases in loneliness, which subsequently elevated anxiety levels, ultimately reducing life satisfaction. Cross-lagged path analyses indicated that loneliness and anxiety formed significant sequential pathways linking SVA to life satisfaction. The model fit indices are as follows: [chi 2((9,N= 234)) = 33.64, chi 2/df = 3.74, p < .001; NFI = .97; IFI = .98; TLI = .93; CFI = .98; SRMR = .06]. These results highlight the cascading psychosocial consequences of excessive short video use and emphasize the importance of longitudinal approaches in digital media research. The study contributes to delineating the longitudinal mechanisms linking digital addiction to subjective well-being and provides a foundation for interventions aimed at mitigating the negative psychological effects of SVA.
Keywords: Short video addiction; loneliness; anxiety; life satisfaction; longitudinal study; MENTAL-HEALTH; MEDIATION; MODELS; Psychology